(untitled) (Jalalabad Medical Journal, 2026)
Perforation is a common complication of peptic ulcers. Due to rapidly spreading peritonitis, perforation is a life-threatening complication of peptic ulcer disease. It is associated with a high rate of mortality and morbidity. It needs prompt resuscitation and urgent, appropriate surgical management to reduce morbidity and mortality. This prospective observational study was conducted in the Department of Surgery, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from January 2021 to December 2023 to see early postoperative complications of duodenal ulcer perforation. Sixty duodenal ulcer perforations underwent open repair with omental patch and aged 18 to 60 years were enrolled. All patients were male. The mean age of the patients was 36.43±8.02 years (range, 24-60 years) and 46.7% were within the 31 to 40 years age group. Fifty percent of patients came to the hospital after 48 hours of symptoms. Site of the perforation was in the anterior wall of the first part of the duodenum in all cases. Peritoneal fluid was purulent (80.3%), fibrinous (10%) and bilious (6.7%). The size of the perforation was between 5 to 10 mm in 58.3% of cases, <5 mm in 21 35% and >10 mm in 6.7% of cases. Early postoperative complications were pneumonia (35%) followed by wound infection (28.3%). Mortality was 1.7%. The mean length of postoperative hospital stay was 10.28±2.92 days (range, 4-22 days). In most of the cases, the duration of operations was within 60 to 75 minutes (46.7%). In conclusion, duodenal ulcer perforation is more common in males and young adults. Early postoperative complications are high. Pulmonary infection and wound infections are the most common complications. Jalalabad Med J 2025; 22 (1): 23-27.